Luis Berges Roldán: Reflections on heritage, thought, and memory through his drawings - Estepa Rubio, Antonio; Estepa Rubio, Jesús (Estoa. Journal of the Faculty of Architecture and Urbanism, 2024)
With this study, we aim to emphasize the heritage of Jaén through the graphic production of architect Luis Berges Roldán. Throughout his professional career, Berges has employed a distinctive and personal system of expression that grants him a recognizable identity. Drawing has always been the lens through which he filters his approach to time and space. The local culture that sparked his vocation as an architect and upon which his executed work unfolds, along with the historical, familial, and personal circumstances he has had to respond to, have been the substrate where his production, both graphic and architectural, has germinated. In this research, we address two complementary perspectives. Firstly, we assess the significance of graphic representation as a substantial asset for understanding his personal universe. Secondly, we focus on comprehending the value of his graphic and architectural production as an inseparable unit, giving rise to his creative thinking.